2006
DOI: 10.4049/jimmunol.177.6.4064
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Induces Eotaxin-1/CC Chemokine Ligand 11 Expression in Human Airway Smooth Muscle Cells: Role of MAPK (Erk1/2, JNK, and p38) Pathways

Abstract: Recently, IL-17A has been shown to be expressed in higher levels in respiratory secretions from asthmatics and correlated with airway hyperresponsiveness. Although these studies raise the possibility that IL-17A may influence allergic disease, the mechanisms remain unknown. In this study, we investigated the molecular mechanisms involved in IL-17A-mediated CC chemokine (eotaxin-1/CCL11) production from human airway smooth muscle (ASM) cells. We found that incubation of human ASM cells with rIL-17A resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 63 publications
8
96
2
1
Order By: Relevance
“…Because Stat3 could be phosphorylated by activated ERK1/2, JNK, or p38 (at Ser 727 ), we further investigated which MAPK pathway may be involved. We observed that ERK1/2, p38, and JNK exhibit time-dependent phosphorylation in HSCs upon IL-17A restimulation, and their response to rmIL-17A restimulation is rapid (within 30 min), like previously observed in human airway smooth muscle cells (45,46). Furthermore, pharmacological inhibition of ERK1/2 or p38 decreased collagen and a-SMA expression in rmIL-17A-challenged or quiescent HSCs.…”
Section: Discussionsupporting
confidence: 60%
“…Because Stat3 could be phosphorylated by activated ERK1/2, JNK, or p38 (at Ser 727 ), we further investigated which MAPK pathway may be involved. We observed that ERK1/2, p38, and JNK exhibit time-dependent phosphorylation in HSCs upon IL-17A restimulation, and their response to rmIL-17A restimulation is rapid (within 30 min), like previously observed in human airway smooth muscle cells (45,46). Furthermore, pharmacological inhibition of ERK1/2 or p38 decreased collagen and a-SMA expression in rmIL-17A-challenged or quiescent HSCs.…”
Section: Discussionsupporting
confidence: 60%
“…To date, only CXCL-8, eotaxin/CCL-11, and 8-isoprostane, a biomarker of oxidative stress, have been identified as inducible products from IL-17 stimulation on HASMC in vitro (34,35,42,46). Although IL-6 superinduction and protein synthesis have been observed in cotreated conditions of IL-17 and TNF-␣, IL-17 alone or in combination with IL-1␤ fails to synergize IL-6 or GM-CSF production after 24 h (16).…”
Section: Discussionmentioning
confidence: 99%
“…The JAK-STAT pathway has also been implicated in IL-17 signaling ( [95,104,141] and R. Wu, personal communication) although activation of these factors is weak compared to Type I or II hematopoietic receptors, and could be indicative of secondary responses to IL-17-induced cytokines. Moreover, IL-17 can induce gene expression in STAT-1-deficient cells [142], and there is evidence against a role for tyrosine kinases in IL-17 gene regulation [79].…”
Section: 33mentioning
confidence: 99%
“…In addition, some CC chemokines are also targets of IL-17, including CCL2/MCP-1 [76,93,94], CCL11/eotaxin [95] and CCL20 [96]. ICAM-1, required for effective neutrophil recruitment to inflamed sites, is also induced by IL-17 [97].…”
Section: Il-17 Regulates Inflammatory Genes Through Synergistic Signamentioning
confidence: 99%